Efektivitas Dana Zakat melalui Program Kampung Zakat di Desa Sulung Kabupaten Sambas Kalimantan Barat - Hairunisah, Rani Pratiwi; Luqman, Luqman; Kalbarini, Rahmah Yulisa (Program Studi Ekonomi Syariah STAI Senori Tuban, 2025)
This research aims to describe the effectiveness of the zakat village program in Sulung Village and analyze the impact of the zakat village program on improving the welfare of the people of Sulung Village. The research method used in this research is qualitative with a descriptive approach. Data collection was obtained from observations, interviews, and documentation. The informants in this research consisted of BAZNAS, the Head of Sulung Village, the village zakat program assistant, the beneficiary community, and the general public. Based on the research that has been carried out, the results obtained show that the effectiveness of the village zakat program is proven by several indicators, namely, first, program understanding, where the community understands and carries out the program well. Secondly, timeliness and targeting, the program carried out is right on target for the mustahiq who needs it, so that it has a real impact that is felt. Third, the goal has been achieved, where BAZNAS' goal of improving the welfare of the Sulung Village Community has been achieved, and there are even several mustahiq who have transformed into muzakki. The impacts of the zakat village program include the economic impact by increasing community income and creating economic stability, the social impact where the sense of tolerance and cooperation increases among the community, and the educational and health impact, which can facilitate access to health and education.